'It's not all fun': Introducing digital technology to meet the emotional and mental health needs of adults with learning disabilities. Issue 2 (3rd April 2017) - Hallas, Penny; Cleaves, Lydia
ABSTRACT: A project that began with an aspiration to introduce digital technologies into an arts therapies service turned into arts therapies taking a lead on these being introduced across all professions and services in a National Health Service (NHS) Learning Disabilities Service. This article can only give limited details of the project as a whole; rather, consideration is given to the benefits of digital technologies to adults with a learning disability, with particular focus on gesture-based technologies. Project design and methodology are described, followed by brief accounts of gesture-based technology (GBT) used across the spectrum of arts engagement and art therapy. Data from qualitative outcome measures inform discussion of the impact of and potential for gesture-based technology in arts therapies practice. In conclusion, we recommend areas for further investigation, and perhaps encourage others to overcome systemic barriers to introducing digital innovation.